National human rights institutions engaging with human rights monitoring mechanisms of the United Nations: comparative assessment - Rutai, Zsuzsanna (Pécs journal of international and European law, 2021)
National human rights institutions are the guardians of human rights at local, regional, national and international level. Their work done in the field justifies their role in international monitoring mechanisms, while their international advocacy supports and strengthens their efforts and impact in their home country. The purpose of the study is to analyse the trends how NHRIs engage with the UN human rights monitoring structure based on the statistics without looking into the content of their submissions and the impact of their engagement.